The Dynamic Role of FOXP3+ Tregs and Their Potential Therapeutic Applications During SARS-CoV-2 Infection - Xu, Zhan; Jiang, Xue; Dai, Xueyu; Li, Bin (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) has been raging all around the world since the beginning of 2020, and leads to acute respiratory distress syndrome (ARDS) with strong cytokine storm which contributes to widespread tissue damage and even death in severe patients. Over-activated immune response becomes one of the characteristics of severe COVID-19 patients. Regulatory T cells (Treg) play an essential role in maintaining the immune homeostasis, which restrain excessive inflammation response. So FOXP3+ Tregs might participate in the suppression of inflammation caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Besides suppressive function, tissue resident Tregs are also responsible for tissue repair. In this review, we mainly summarize the latest research focusing on the change of FOXP3+ Tregs in the COVID-19 patients, discuss the relationship between disease severity and number change of Tregs and speculate the potential role of FOXP3+ Tregs during SARS-CoV-2 infection. Furthermore, we introduce some potential Treg-based therapies to improve patients’ outcomes, which include small molecular drugs, antibody drugs, CAR-Treg and cytokine treatment. We hope to reduce tissue damage of severe COVID-19 patients and offer better prognosis through Treg-based therapy.